2021
DOI: 10.3389/fpsyg.2021.635816
|View full text |Cite
|
Sign up to set email alerts
|

Can Yogic Breathing Techniques Like Simha Kriya and Isha Kriya Regulate COVID-19-Related Stress?

Abstract: The global impact of Coronavirus Disease 2019 (COVID-19) is tremendous on human life, not only affecting the physical and mental health of population but also impacting the economic system of countries and individual itself. The present situation demands prompt response toward COVID-19 by equipping the humans with strategies to overcome the infection and stress associated with it. These strategies must not only be limited to preventive and therapeutic measures, but also aim at improving immunity and mental hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 138 publications
0
3
0
Order By: Relevance
“…Alternatively, these outcomes may require more than 4 weeks of practice and particularly high levels of adherence (e.g., 5-7 days a week) (Tunuguntla et al, 2021). It is also possible that these outcomes require different types of yoga and meditation practices altogether; for example, Isha Kriya, which involves mental noting, breathwork, and yoga of sound, was found to stabilize mood disturbances among healthcare professionals (Rangasamy et al, 2019) and may regulate COVID-19 related stress (Rain et al, 2021). At the same time, the potential strengths of the intervention's current 4-week practice structure should be considered; the fact that the students experienced relief within a relatively short time frame suggests that this intervention may be especially suited to helping students manage common forms of short-term stress (e.g., preparing for final exams and dissertation defenses).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, these outcomes may require more than 4 weeks of practice and particularly high levels of adherence (e.g., 5-7 days a week) (Tunuguntla et al, 2021). It is also possible that these outcomes require different types of yoga and meditation practices altogether; for example, Isha Kriya, which involves mental noting, breathwork, and yoga of sound, was found to stabilize mood disturbances among healthcare professionals (Rangasamy et al, 2019) and may regulate COVID-19 related stress (Rain et al, 2021). At the same time, the potential strengths of the intervention's current 4-week practice structure should be considered; the fact that the students experienced relief within a relatively short time frame suggests that this intervention may be especially suited to helping students manage common forms of short-term stress (e.g., preparing for final exams and dissertation defenses).…”
Section: Discussionmentioning
confidence: 99%
“…Rangasamy et al (2019) found that a beginner's meditation called Isha Kriya meditation may improve mood among health professionals. Another beginner's practice called Simha Kriya showed feasibility and acceptance among healthcare workers during the COVID-19 pandemic (Narayanan et al, 2021) and may reduce COVID-19 related stress (Rain et al, 2021). A randomized control study showed that the IEO program, including the system of Upa Yoga, reduced stress among technology professionals (Upadhyay et al, 2022).…”
Section: Early Evidence On the "Inner Engineering" Methodsmentioning
confidence: 99%
“…Yoga-based breathing practices were found to help improve vagal tone and had a positive effect on mental health [ [19] , [20] , [21] , [22] , [23] ]. Yoga-based breathing practices had an impact on these practices in reducing the psychiatry manifestations [ 24 , 25 ]. Yoga-based breathing practices (Pranayama) are focused on breathing patterns, which promote mindfulness and mental health [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%